A Structural Model of Export versus Affiliates Production - Jörn Kleinert; Farid Toubal (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2005)
We derive and estimate an econometric model of export versus foreign production using firm-level data on foreign activities of German multinationals. Proximity-concentration theory which we derive our model from shows that firms face a trade-off between concentrating their production at home to save on plant set-up costs and producing abroad to save on distance costs. Firms facing this trade-off choose between export and foreign production according to their expected profits. The model is brought to the data using a pooled-probit analysis over the period 1996-1999. We find support for the proximity-concentration trade-off. In particular, market size and distance affect positively the probability of foreign production whereas fixed costs have a negative impact on the decision to engage in FDI.
urn:nbn:de:bsz:21-opus-18229
Keywords: F12; F23; 330; Multinational firms; trade; Multinationales Unternehmen; Exportindustrie; Auslandsproduktion; Landesgrösse; Transportkosten; Schätzung; Deutschland; Proximity-concentration theory